1998
DOI: 10.1021/jm970741j
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Selective 5-HT2C/2B Receptor Antagonists as Potential Anxiolytic Agents:  Synthesis, Quantitative Structure−Activity Relationships, and Molecular Modeling of Substituted 1-(3-Pyridylcarbamoyl)indolines

Abstract: The synthesis, biological activity, and molecular modeling of a novel series of substituted 1-(3-pyridylcarbamoyl)indolines are reported. These compounds are isosteres of the previously published indole urea 1 (SB-206553) and illustrate the use of aromatic disubstitution as a replacement for fused five-membered rings in the context of 5-HT2C/2B receptor antagonists. By targeting a region of space previously identified as sterically allowed at the 5-HT2C receptor but disallowed at the 5-HT2A receptor, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 34 publications
2
74
0
Order By: Relevance
“…5-HT 2C R-allowed and 5-HT 2A R-disallowed volumes (gray oval), marked around the structure of compound 90 [68]. study, the proposed ligand binding mode to the 5-HT 2C receptor was further validated by the CoMFA approach [69]. All derivatives (55) were docked into the receptor model, and after brief energy minimization of each ligand-receptor complex, individual compounds were extracted and subjected to the CoMFA analysis.…”
Section: Ravina Et Al Investigated a Series Of 28 (Aminoalkyl) Benzomentioning
confidence: 99%
“…5-HT 2C R-allowed and 5-HT 2A R-disallowed volumes (gray oval), marked around the structure of compound 90 [68]. study, the proposed ligand binding mode to the 5-HT 2C receptor was further validated by the CoMFA approach [69]. All derivatives (55) were docked into the receptor model, and after brief energy minimization of each ligand-receptor complex, individual compounds were extracted and subjected to the CoMFA analysis.…”
Section: Ravina Et Al Investigated a Series Of 28 (Aminoalkyl) Benzomentioning
confidence: 99%
“…For example, antagonists with higher affinity for the 5-HT 2C/2B receptor than the 5-HT 2A receptor display anxiolytic-like profiles in a number of animal models. Thus, SB-206553, SB-200646A and SB-221284 reduce anxiety in a range of paradigms including the EPM, social interaction and Geller Seifter tests (Kennett et al 1994(Kennett et al , 1995(Kennett et al , 1996Griebel et al 1997;Bromidge et al 1998). Both SB-206553 and SB-242084, the latter a selective 5-HT 2C antagonist with over 100 fold selectivity for 5-HT 2C over 5-HT 2B and 5-HT 2A receptors (Kennett et al 1997), block the anxiogenic profile of an acute dose of the selective serotonin reuptake inhibitor (SSRI) citalopram in the rat social interaction test, whereas the 5-HT 2A antagonist MDL 100907 does not (Dekeyne et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Cyamemazine also behaves as a potent antagonist at 5-HT 2C -receptors, an effect that can contribute to its anxiolytic activity since: (i) in humans, ritanserin appears to be an effective anxiolytic agent (Ceulemans et al 1985;see, however, Deakin et al 1991) and (ii) recent pharmacological studies have suggested an anxiolytic potential for 5-HT 2C -receptor antagonists (Griebel et al 1997;Kennet et al 1997;Bromidge et al 1998). The present data indicate that cyamemazine displays a high affinity (K i =27 nM) for 5-HT 2C receptor sites in rat brain and acts as a moderate potency (K i =424 nM) 5-HT 2C antagonist in functional signal transduction assays.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies also revealed anxiolytic potential for 5-HT 3 -receptor antagonists (for review see Costall and Naylor 1992), and some recent clinical trials revealed anxiolytic efficacy for the 5-HT 3 -antagonists tropisetron and ondansetron (although studies with ricasetron were inconclusive; for review see Bentley and Barnes 1995). Even more recently, pharmacological studies have suggested an anxiolytic potential for 5-HT 2C -receptor antagonists (Kennett et al 1997;Bromidge et al 1998).…”
Section: Introductionmentioning
confidence: 99%